(untitled) (Research, Society and Development, 2022)
A dam is a structure built across a valley whose function is to contain water or waste from a production process. This study aimed to gather information about the construction of earth and earth dams with rockfill to contain mining and water tailings, with emphasis on the most common raising construction models in Brazil. In this sense, a literature review was conducted based on qualitative descriptive research focusing on bibliographic materials that study the constructive issues of the heightening of this type of work. These constructions have three executive methods for the containment of tailings, one of raising downstream, upstream and at the center line, and one, the one-off raising, for the damming of water. Both must follow the criteria established for the construction of the earth or rock mass, using suitable materials, and carrying out the compaction with monitoring of laboratory tests, to ensure that the landfill has good structural performance. Furthermore, it is extremely important to design the external drainage system to avoid soil erosion around the building and to prevent disasters. The main causes of dam failure include the absence of continuous monitoring, austere control during its construction/operation and deficiency of the drainage system. It was found, therefore, that to make the appropriate choice of the constructive model of the dam heightening, its purpose must be analyzed, in addition to carrying out continuous monitoring and, if necessary, decommissioning, deactivation or de-characterization.